Peningkatkan Hasil Belajar Peserta Didik Pada Materi ciri-Ciri Khusus yang Dimiliki Hewan Melalui Model Integratif di Kelas VI Tahun Pelajaran 2022/2023 SDN 12/X Pemusiran - Sulisman Sulisman (Departement of Mathematics Education, 2023)
The implementation of good Science learning depends on the way the teacher presents the material, manages the class and uses active and creative learning models, one of which is the Integrative learning model which is an effective way to vary the atmosphere in discussion and collaboration in class so that students are motivated to learning. This study aims (1) to determine the teacher's ability to develop material on the special characteristics of animals through an integrative model. (2) To find out the activities of students on the special characteristics of animals through the integrative learning model. (3) Knowing the learning outcomes of students through material special characteristics possessed by animals through the Integrative model. This study uses quantitative classroom action research. The data from this research were obtained by using (1) Observation sheets on teacher abilities and student activities. (2) data analysis using percentage formula. The research results obtained were, the ability of teachers increased from 82% in the first cycle to 91% in the second cycle. Student activity increased from 88% in cycle I to 94% in cycle II Based on the results of the study it can be concluded that with the integrative model in learning Science students are more active, and their learning outcomes increase.